Numerical Analysis of Melting Process in a Rectangular Enclosure with Different Fin Locations - Huang, Bin; Tian, Lin-Li; Yu, Qing-Hua; Liu, Xun; Shen, Zu-Guo (Energies (Basel), 2021)
Latent thermal energy storage is regarded as an effective strategy to utilize solar energy and recover automotive waste heat. Based upon an enthalpy-porosity method, the influence characteristics and mechanism of fin location on phase change material melting behavior in vertical rectangular enclosures were explored numerically. The results show that as fin location increases, the melting time decreases before attaining the minimum at the fin location of 0.20 after which it increases and finally surpasses the no fin case, because (1) the influence range of fins for conduction is limited by the bottom surface when putting fins next to this surface, (2) the liquid flow resistance increases with moving fins up, and (3) mounting fins near the top surface accelerates melting at the upper part, facilitating thermal stratification formation and weakening natural convection. Nu is higher than the no fin case, i.e., Nu enhancement factor is a positive value, in the melting process for a lower fin location, while for other fin locations, a transition to a negative value takes place. The higher the fin location is, the earlier the transition that arises. Finally, a strategy of increasing the maximum liquid flow velocity is proposed to reinforce melting for cases with considerable natural convection.